Penguatan Pemasaran dan Inovasi Produk UMKM Makanan melalui Pengembangan Kapasitas SDM dan Adaptasi Tren Pasar Desa Ngargogondo - Verawati, Dian Marlina; Widayanti, Ipuk; Achsa, Andhatu; Paska, Yesica Apriliana; Jannah, Nurul; Ridho, Rizky (ABDIMASKU : Jurnal Pengabdian Masyarakat UTND, 2025)
The purpose of this community service program is to strengthen marketing capacity and product innovation among food MSMEs in Ngargogondo Village in order to adapt to market trends and enhance competitiveness. The program was implemented using a participatory approach, including training on digital marketing management, assistance in developing consumer-oriented product innovations, and human resource capacity building through workshops and practical simulations. The results show an increased understanding of digital marketing strategies, the emergence of several new product variations aligned with market trends, and improved confidence among entrepreneurs in expanding their marketing networks. In conclusion, this program successfully enhanced MSME human resource capacity, fostered product innovation, and created greater opportunities for market. expansion